Clinical Efficacy of Subhypothermia in the Treatment of Neonatal Hypoxic-Ischemic Encephalopathy Combined with Myocardial Damage - XiaoPing Dang; XiaoJian Hu; Xun Jiang; WeiGuo Chen; YuanCui Meng; Qi Pan; Fen Yang (Adsorption Science & Technology)
Objective. To investigate the efficacy of subhypothermia in the treatment of neonatal hypoxic-ischemic encephalopathy (HIE) combined with myocardial damage. Methods. 136 children with HIE and myocardial damage admitted to our hospital from October 2019 to October 2021 were included in the study and were divided into study group and control group of 68 cases each according to the random number table method. The control group was given conventional treatment, and the study group was treated with subhypothermia therapy on top of the control group. Comparing the effects of treatment between the two groups. The serum levels of S-100β protein, Tau protein, neuron-specific enolase (NSE), creatine kinase (CK), creatine kinase isoenzyme MB (CK-MB), lactate dehydrogenase (LDH), alpha-hydroxybutyrate dehydrogenase (ɑ-HBDH), myoglobin (Myo), cardiac trophic factor-1 (CT-1), cardiac troponin I (cTnI), superoxide dismutase (SOD), reactive oxygen species (ROS), glutathione peroxidase (GSH-Px), interleukin-1β (IL-1β), interleukin-8 (IL-8), and tumor necrosis factor-ɑ (TNF-ɑ) were measured in both groups before and after treatment, respectively. Results. The total effective rate was higher in the study group (88.24%) than in the control group (72.06%) (P<0.05). After treatment, the serum levels of S-100β protein, Tau protein, NSE, CK, CK-MB, LDH, ɑ-HBDH, Myo, CT-1, cTnI, ROS, IL-1β, IL-8, and TNF-ɑ were reduced in both groups, and the study group was lower than the control group (P<0.05). The serum levels of SOD and GSH-Px were higher in both groups after treatment than before treatment and were higher in the study group than in the control group (P<0.05). Conclusion. Subhypothermia treatment of children with HIE combined with myocardial injury can further improve the hypoxic-ischemic state; reduce myocardial damage, oxidative stress, and inflammatory response; and has a good overall efficacy.